STUDI KOMPARASI VARIASI JENIS SUPERPLASTICIZER TERHADAP SIFAT MEKANIS BETON MUTU TINGGI DENGAN MENGGUNAKAN FLY ASH ABU CANGKANG KELAPA SAWIT SEBAGAI ADITIF - Zulham Effendi; Taufik Saidi; Teuku Budi Aulia (Prodi Magister Teknik Sipil Unsyiah, 2018)
Nowadays, a construction uses a lot of concrete with highly strong power that is needed to support materials supporting the construction. With the improvement of concrete technology nowadays it is possible that high quality concrete with the suppression of greater than 70 MPa. Aceh Province, which is located, at the most tip of Sumatera Island has a great number of natural resources and materials that can be used in order to make concrete. These available resources are used for making high quality concrete with the pressure of 70 MPa. This research is going to explore the characteristic of concrete mechanic comprises of the strength of its pressure, the strength of its tight pressure, the bow strength and the sliding strength that can be reached by using additional material of palm nutshell as an additife replacement as apart of concrete use and the variation of the variety of superplasticizer optimum percentage of Sikament LN, Sikament NN and Viscocrete-10 by rude aggregation with maximum measure is12 mm. its concrete is used as Portland concrete type I with vary kinds of superplasticizer by each maximum percentage of Sikament LN is 1%, Sikament NN 1,5% and Viscocrete-10 1,5 % . the factor of water concrete is 0,3 and the amount of palm nutshell dust as an aditif that is used is 10%. The value of pressure and tight breaking strenght, flexibility tight strengh and sliding strenght from third variaties of superplasticizer, namely Viscocrete-10 with the percentage is 1,5% having bigger valuecompred to Sikament NN 1,5% and Sikament LN 1,0%. In terms of testing hot hydration the result shows that the viscocrete – 10 has been able earlier to prevent hot hydration with value is 6 hour; 24oC compared to Sikament NN 8 hour; 240C and the kind of Sikament LN 78 hour; 250C.